QUALIDADE DE VIDA EM PORTADORES DE INSUFICIÊNCIA RENAL CRÔNICA (IRC) QUE NÃO REALIZAM HEMODIÁLISE - Fassbinder, Tânia R. C.; Gerhardt, Catieli C.; Dallazen, Fernanda; Basso, Olvânia; Belli, Karlyse C.; Winkelmann, Eliane R. (Salão do Conhecimento, 2013)
Resumo